Characterization of small (⩽3 cm) hepatic lesions with atypical enhancement feature and hypointensity in hepatobiliary phase of gadoxetic acid-enhanced MRI in cirrhosis: A STARD-compliant article. Issue 29 (July 2017) - Shin, Seung Kak; Kim, Yun Soo; Choi, Seung Joon; Shim, Young Sup; Jung, Dong Hae; Kwon, Oh Sang; Choi, Duck Joo; Kim, Ju Hyun
Abstract : Abstract: It is difficult to characterize the nodular lesions in cirrhotic liver if typical enhancement pattern is not present on dynamic contrast-enhanced imagings. Although the signal intensity of the hepatobiliary phase in gadoxetic acid-enhanced magnetic resonance imaging (MRI) is helpful for characterization of the lesions, some dysplastic nodules may also exhibit low signal intensity in the hepatobiliary phase. We aimed to assess the usefulness of gadoxetic acid (Gd-EOB-DTPA)-enhanced MRI including diffusion-weighted imaging (DWI) for differentiation between atypical small hepatocellular carcinomas (HCCs) and dysplastic nodules showing low signal intensity (SI) in the hepatobiliary phase, and to evaluate the MRI findings in determining the histological grade of atypical HCCs in patients with cirrhosis. A total of 43 cirrhotic patients with a small (⩽3 cm) liver nodule (n = 25, HCC; n = 18, dysplastic nodule) who underwent Gd-EOB-DTPA-enhanced MRI and pathologic confirmation were retrospectively reviewed. Atypical HCC was defined as not showing arterial hyperenhancement and delayed washout on dynamic MRI. High SI on both T2WI and DWI (sensitivity 80.0%, specificity 100%, positive predictive value 100%, negative predictive value 78.3%) was the most specific feature to differentiate atypical HCCs from dysplastic nodules. High SI on both T2WI and DWI (100% vs 61.5%, P = .039) or low SI on pre-enhanced T1WI (83.3% vs 30.8%, P = .021) was more frequent observed in Edmonson grade II–III HCCs compared with those in grade I HCCs. The combination of DWI and T2WI is most useful for the differentiation of atypical small HCCs from dysplastic nodules showing low SI in the hepatobiliary phase. Combination of DWI and T2WI or pre-enhanced T1WI seems to be useful for predicting the histological grade of atypical HCCs.